The Analysis of Network Actors in the Policy Implementation of Developing Tourism in Semarang City - YUNININGSIH, Tri; SUWITRI, Sri; KISMARTINI, KISMARTINI; SOESILOWATI, Etty (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).10, 2019)
There aren’t optimal development and management efforts the object and tourist attraction. Yet its optimal development of tourist destinations. Yet it’s optimal participation of the private and the public in the development of tourism. It is becoming an indication of the importance of the network actors study in the policy implementation of tourism development in Semarang City. This research applies qualitative descriptive analysis. The technique uses key informant selection of informants, namely the Department of culture and tourism in Semarang City. The results showed that the policy implementation of tourism development in Semarang city hasn’t run with optimal. It is characterized by the role of the actors involved have not been able to work together. As it doesn’t yet optimal role of Semarang Tourism Promotion Agency is known as BP2KS. In addition, the presence of distrust among the actors involved. In the findings of the field, the concept of development of tourism in Semarang City is using model Pentahelix, including academia, business, Government, community and the Mass Media. Fore the need to immediately increase communication and coordination and transparency among the actors, among others through the forum gatherings and public hearing. Further strengthen the institutional function BP2KS. Need to be calculated as a sense of belonging “the soul of the region’s wisdom".